2009
DOI: 10.1002/jso.21401
|View full text |Cite
|
Sign up to set email alerts
|

Routine or on demand radiological contrast examination in the diagnosis of anastomotic leakage after esophagectomy

Abstract: Our study suggests that the clinical value for a routinely performed contrast examination is debatable. We recommend performing a contrast examination based on clinical suspicion and clinical signs of anastomotic leakage including sepsis, fever > or = 39.0 degrees C and leukocytosis > or = 20 x 10(9)/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The earliest patient to be diagnosed by endoscopy suffered an AL 5 days after the operation. A total of 6 patients were diagnosed by performing a contrast study after clinical suspicion of AL, as recommended by Honing et al [22]. Four patients were diagnosed using methylene blue, indicating that this technique nowadays has only a limited significance but can be applied in selected cases such as in patients with early suspicious secretion from the peri-anastomotic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest patient to be diagnosed by endoscopy suffered an AL 5 days after the operation. A total of 6 patients were diagnosed by performing a contrast study after clinical suspicion of AL, as recommended by Honing et al [22]. Four patients were diagnosed using methylene blue, indicating that this technique nowadays has only a limited significance but can be applied in selected cases such as in patients with early suspicious secretion from the peri-anastomotic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, more recent studies seem to suggest that swallows should only be performed on clinical concern because of the low sensitivity of this method for detecting leaks. [11][12][13] The evidence to support the use of routine contrast swallows is lacking and some studies have shown that swallows should only be requested in cases where an anastomotic leak is suspected clinically.…”
Section: Other Literaturementioning
confidence: 99%
“…These complications should be detected and managed immediately because the complications can be fatal if the detection is delayed. However, most anastomotic sites are inside the body; therefore, evaluation of anastomosis has to be performed by indirect methods, physical findings, blood test, X-ray, computed tomography, or contrast swallow [6,7]. …”
Section: Discussionmentioning
confidence: 99%